ANALISIS PERUBAHAN PENGGUNAAN LAHAN DI KAWASAN TAMAN HUTAN RAYA SULAWESI TENGAH MENGGUNAKAN CITRA LANDSAT DI KELURAHAN TONDO KECAMATAN PALU TIMUR KOTA PALU PROVINSI SULAWESI TENGAH - Moniaga, Inrawati; Hamzari, Hamzari; Arianingsih, Ida (Jurnal Warta Rimba, 2015)
Forest park as a part part conservation forest is determined to be free from any activities particularly from encroachment and other uses.A result of human intervention in these changes, then, formed various types of land use, among others: the protected areas such as primary and secondary forests; area cultivated for food needs such as mixed farms / plantations, fields; the area of a former forest or agricultural land clearing as shrubs and reeds; and the area used for human habitation, and this will greatly affect broad change, vegetation density above and below the vegetation density, which in turn affects the damage due to soil erosion in an area. Those activities mentioned above are not only creating the loss of forest but also impacting degradation resulted from farming carried out by community living around. Such activities were found to happen in Forest Park in Tondo, East Palu, Palu, Central Sulawesi. The objectives of the study is to identify the land use change from 2007 to 2013 of Central Sulawesi Forest Park use landsat imagery 7ETM+ and landsat imagery 8 +ETM. The study method used was classification, by classifying the change of land from the aforementioned period of time 2007-2013 in Forest Park in Tondo, East Palu, Palu, Central Sulawesi. The study took place in Tondo as part of the forest park conducted from March to June 2014. The results of the study found that the largest land use change happens in Forest Park in Tondo, East Palu, Palu, Central Sulawesi the secondary forest, i.e., from 1,211.95 ha in 2007 down to 1,165.95 ha in 2013. This happens due to various factors in Forest Park in Tondo, East Palu, Palu, Central Sulawesi the open garden for primarily from farming and animal feeding activities carried out by the coomunity surrounding Keywords: Analysis, Land Use, Central Sulawesi Forest Park.